Expression Analyses of ABCDE Model Genes and Changes in Levels of Endogenous Hormones in Chinese Cabbage Exhibiting Petal-Loss - Chuan MENG (Horticultural Plant Journal, 2017)
Abnormal formation of floral organs affects plant reproduction and can directly interfere with the progress of breeding programs. Using PCR amplification, ABCDE model genes BraAP2, BraAP3, BraPI, BraAG, BraSHP, and BraSEP were isolated from Chinese cabbage (Brassica rapa L. ssp. pekinensis). We examined six development stages of floral buds collected from Chinese cabbage and compared between a line demonstrating normal flowering (A-8) and two mutated lines that exhibited plants having petal-loss (A-16 and A-17). The expression of ABCDE model genes has been analyzed by qRT-PCR. Compared with flower buds of petal-loss plants and normal plants, the expression of A-class gene BraAP2 was significantly decreased during the first to fourth stages, C-class gene BraAG expression was significantly decreased during the first to fifth stages, and D-class gene BraSHP expression was significantly decreased during the first to third stages. Furthermore, B-class gene BraAP3 and BraPI and E-class gene BraSEP expressions were significantly decreased during all six stages of petal-loss plants compared with normal plants. Enzyme-linked immunosorbent assays detected nine endogenous phytohormones during all stages examined here. Except for the second-stage and third-stage buds, levels of the auxin IAA and cytokinin dhZR were always higher in the petal-loss plants than the normal plants at corresponding time points. Meanwhile, concentrations of GA1+3 at the first, fourth, and fifth stages were higher in the petal-loss plants than in the normal plants. Our results provide a theoretical basis for future exploration of the molecular mechanism that determines petal loss and the effects that hormones have on such development in Chinese cabbage plants.